The Role of the Hikayat Tradition in the Moral and Cultural Education of the Sasak Community - Saeti, Muhammad; Sulhan Hadi, Muh.; Eka Saputra, Bambang; Murcahyanto, Hary (IJE : Interdisciplinary Journal of Education, 2025)
This research explores the role and preservation of the Hikayat tradition in Denggen Village, Selong District, Lombok, and its impact on the community. Using a qualitative approach, the study involved in-depth interviews with 12 informants, including local community members, pembayun (hikayat readers), and traditional leaders, selected for their deep knowledge of the Sasak culture and tradition. The findings reveal that the Hikayat tradition serves key functions: as a medium for da’wah (religious preaching), moral education, and the preservation of cultural values. It also plays a critical role in fostering solidarity and strengthening social ties during traditional events. Despite challenges posed by globalization, the community continues to adapt the Hikayat tradition, modifying its delivery methods and incorporating translations to maintain its relevance. Concrete recommendations for its preservation include greater community involvement and targeted government support for cultural initiatives, ensuring the Hikayat’s sustainability in modern times